Kunst en Handicap : BuitenGewóón - Oog-in-oog in dialoog! - Aerts, Gilbert; Beelen, Yvonne; D'Joos, Marleen; Dethier, Hubert; Focquet, Joost; Gils, Lou; Seynhaeve, Dirk; Van Craenenbroeck, Patrick; Vollekindt, Robert & Rita; Kasteel Borluut Sint-Denijs-Westrem (Brussel : Vlaamse Federatie van Gehandicapten, 1998)
Beckx, Julia ; Bomans, Frank ; Boone, Luc ; Boven, Kathleen ; Claes, Ann ; Coppens, Eric ; Cuypers, Katrien ; Daemen, Patrick ; De Beuckelaer, Tom ; De Block, Magda ; De Bruyn, Wilfried ; Decamps, Jan ; De Koninck, Fons ; De Wispelaere, Leonie ; Gooverts, Rosette ; Grace, Dehlia ; Hendrickx, Nathalie ; Hingst, Wytze ; Hofman, Ronald ; Holemans, Yael ; Indeherberge, George ; Junius, Albert ; Laverge, Pascal ; Leytens, Sara ; Maguin, Pascal ; Moons, Marie-Josee ; Nijnen, Esther ; Osselaer, Henri ; Rutten, Patrick ; Seymons, Chris ; Smet, Suzanne ; Soens, Veronique ; Spannaghe, Katia ; Timmermans, Eddy ; Tyncke, Hilde ; Vandenbrande, Philemon ; Van Haren, Edwin ; Vanhessche, Mieke ; Van Loon, Ank ; Verelst, Etienne ; Verheyden, Fons ; Verheyden, Paul ; Volckaert, Christiaan ; Vollekindt, Ann ; Wostijn, Andre
Kunst en Handicap : BuitenGewóón - Oog-in-oog in dialoog!, Kasteel Borluut Sint-Denijs-Westrem, 05 - 20.12.1998
Nederlands
boek